Answer:
j = 8
Explanation:
simplifying
2(3j + -4) + -7 = 3j + 1 + j
Reorder the terms:
2(-4 + 3j) + -7 = 3j + 1 + j
(-4 * 2 + 3j * 2) + -7 = 3j + 1 + j
(-8 + 6j) + -7 = 3j + 1 + j
Reorder the terms:
-8 + -7 + 6j = 3j + 1 + j
Combine like terms: -8 + -7 = -15
-15 + 6j = 3j + 1 + j
Reorder the terms:
-15 + 6j = 1 + 3j + j
Combine like terms: 3j + j = 4j
-15 + 6j = 1 + 4j
Solving
-15 + 6j = 1 + 4j
Solving for variable 'j'.
Move all terms containing j to the left, all other terms to the right.
Add '-4j' to each side of the equation.
-15 + 6j + -4j = 1 + 4j + -4j
Combine like terms: 6j + -4j = 2j
-15 + 2j = 1 + 4j + -4j
Combine like terms: 4j + -4j = 0
-15 + 2j = 1 + 0
-15 + 2j = 1
Add '15' to each side of the equation.
-15 + 15 + 2j = 1 + 15
Combine like terms: -15 + 15 = 0
0 + 2j = 1 + 15
2j = 1 + 15
Combine like terms: 1 + 15 = 16
2j = 16
Divide each side by '2'.
j = 8